Characteristics and attitudes of women in relation to chosen fertility preservation techniques: a prospective, multicenter questionnaire-based study with 144 participants. (June 2016) - von Wolff, Michael; Giesecke, Dagmar; Germeyer, Ariane; Lawrenz, Barbara; Henes, Melanie; Nawroth, Frank; Friebel, Stefanie; Rohde, Anke; Giesecke, Peter; Denschlag, Dominik
Abstract: Objective: What are the patients attitudes about their fertility and about the counselling process at the time when fertility preservation counselling is performed? Study design: A survey regarding fertility concerns and counselling performance in relation to the chosen fertility preservation procedure such as no treatment, GnRH agonists, and freezing of ovarian tissue or oocytes/zygotes was prospectively conducted in four university centres and one private centre, all belonging to the network Ferti PROTEKT in Germany and Switzerland. Results: All women ( n = 145) received a questionnaire at the first counselling appointment. The mean age of the patients was 30 years (±5.8, range 17–43 years). 91% were referred by their treating oncologists. Single patients preferred invasive strategies, such as freezing of oocytes/zygotes (44.3%) or freezing of ovarian tissue (36%), whereas only 19.7% opted for no treatment/GnRH agonists. In married couples, the proportions were 28.9%, 31.1% and 40.0% respectively. Women without children also opted more frequently for invasive strategies, such as freezing of oocytes/zygotes (84.5%) or freezing of ovarian tissue (74.1%), and less frequently for no treatment/GnRH agonists (63.3%). Physical and psychological status, current and future fertility concerns and satisfaction with the counselling process were equal in all treatment groups. Conclusion: As fertility concerns and attitudes about the counselling process were independent from the fertility preservation procedure chosen, the preferred treatment can hardly be predicted and therefore all women should be counselled about all possible fertility preservation techniques.